A carbon-coated sodium chromite material and its preparation method and application

By using step-by-step heating and decarbonization method in the preparation of sodium chromite material, the carbon cladding layer is formed, which solves the problem that the material is prone to side reactions during charging and discharging, improves electrochemical stability and cycling performance, and reduces costs.

CN115863609BActive Publication Date: 2025-03-04HUBEI ZHENHUA CHEMICAL CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310009339.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-03
Publication Date
2025-03-04
Estimated Expiration
2043-01-03

AI Technical Summary

Technical Problem

The sodium chromite materials prepared in the prior art are prone to side reactions with the electrolyte during charging and discharging, resulting in structural damage, poor stability and rapid capacity decay.

Method used

The chromium source and sodium source are used as the main raw materials to form a gel through a complexing agent, perform primary decarbonization and secondary decarbonization, and sintering to obtain carbon-coated sodium chromite material. This method achieves carbon coating of sodium chromite material through step-by-step heating and decarbonization, prevents side reactions from occurring, and improves the electrochemical stability and cycling performance of the material.

Benefits of technology

It effectively prevents the occurrence of side reactions, improves the electrochemical stability and cyclic properties of the material, and has good uniformity of the carbon coating layer, which can play the role of a conductive agent, reduces the use of the conductive agent, and reduces the cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115863609B_ABST
    Figure CN115863609B_ABST
Patent Text Reader

Abstract

The present invention provides a carbon-coated sodium chromite material, a preparation method thereof and an application. The preparation method comprises the following steps: 1) mixing a chromium source, a sodium source and a complexing agent to obtain a gel; 2) dehydrating the gel obtained in step 1) to obtain a dry gel; 3) performing primary decarbonization and secondary decarbonization on the dry gel obtained in step 2) successively, and sintering to obtain the sodium chromite material; the temperature of the dehydration is T0, the temperature of the primary decarbonization is T1, the temperature of the secondary decarbonization is T2, and the temperature of the sintering is T3, where T0 < T1 < T2 < T3; the atmosphere of the secondary decarbonization is an oxygen-containing atmosphere. The present invention adopts a stepwise heating decarbonization method for partial decarbonization. The process is simple, low in cost and mild in conditions. It can not only effectively prevent the occurrence of side reactions, but also has good uniformity of the formed carbon coating layer, which can act as a conductive agent, improve the electrochemical stability and cycling performance of the material, and has good application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a carbon-coated sodium chromite material and a preparation method and application thereof. Background Art

[0002] With the advent of the era of electric vehicles and smart grids, the shortage of lithium resources will become an important factor restricting their development. Therefore, it is urgent to develop the next generation of energy storage battery systems with excellent comprehensive performance. The research and development of sodium-ion batteries is expected to alleviate the problem of limited development of energy storage batteries caused by the shortage of lithium resources to a certain extent. In addition to the advantages of abundant and easy-to-obtain sodium resources, low cost and wide distribution, sodium-ion batteries have more safety advantages compared with lithium-ion batteries. The thermal runaway temperature of sodium batteries is higher than that of lithium batteries, and they are more easily passivated and oxidized, and are not prone to spontaneous combustion. However, sodium ions have a larger ionic radius and a slower kinetic rate, which has become the main factor restricting the development of sodium storage materials. The development of high-performance sodium-embedded positive electrode materials is the key to improving the specific energy of sodium-ion batteries and promoting their application. Sodium chromite positive electrode materials (NaCrO 2 ) has excellent performance in terms of working voltage, specific capacity and cycle stability, so the study of NaCrO 2 Cathode materials are of great significance to the practical application of sodium-ion batteries.

[0003] CN103370277B discloses a method for manufacturing a sodium chromite material, which comprises: adjusting the water content of a mixture of chromium oxide powder and sodium carbonate powder to less than 1000 ppm, and then calcining the mixture in an inert gas atmosphere.

[0004] CN114180628A discloses a method for preparing sodium chromite by a vacuum process, comprising: heating and drying chromium oxide powder and sodium carbonate powder, and then mixing them in a certain proportion; vacuum ball milling the mixed powder, and then performing vacuum acoustic resonance mixing treatment, and then pressing them into tablets; placing the mixed tablets in a vacuum reaction furnace for calcination, and then performing low-temperature liquid nitrogen ball milling on the calcined product, and then performing ultrasonic cleaning treatment to obtain sodium chromite.

[0005] CN114195188A discloses a method for preparing high-purity sodium chromite. The method comprises the following steps: firstly, pre-treating chromium oxide by nitric acid-high pressure closed digestion, and pre-treating sodium carbonate by ultrasonic vibration recrystallization purification; mixing the pre-treated chromium oxide and sodium carbonate in a certain proportion, grinding and mixing by ultra-low temperature liquid nitrogen ball milling, and then pressing and forming; then performing high-temperature solid phase reaction under an inert atmosphere; finally, washing the cooled reactant with a polar solvent, filtering, and vacuum drying to obtain high-purity sodium chromite.

[0006] However, the sodium chromite prepared by the above preparation method is prone to side reactions with the electrolyte during the charge and discharge process, causing structural damage to the sodium chromite material, making its stability worse and causing the problem of rapid capacity decay.

[0007] Therefore, designing a method for preparing a sodium chromite material so that the prepared sodium chromite material can reduce the occurrence of side reactions and improve the electrochemical stability and cycle performance of the sodium chromite material is a technical problem that needs to be solved urgently. Summary of the invention

[0008] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a carbon-coated sodium chromite material and a preparation method and application thereof. The present invention provides a preparation method of a carbon-coated sodium chromite material, wherein the preparation method uses a chromium source and a sodium source as main raw materials, adopts a complexing agent to form a gel, performs primary decarburization and secondary decarburization after dehydration, and sintering to obtain the carbon-coated sodium chromite material. This preparation method has simple process, low cost and mild conditions, and partial decarburization is performed by step-by-step heating decarburization to achieve carbon coating of the sodium chromite material, which not only effectively prevents the occurrence of side reactions but also forms a carbon coating layer with good uniformity, which can act as a conductive agent, improve the electrochemical stability and cycle performance of the material, and has good application potential.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a carbon-coated sodium chromite material, the preparation method comprising the following steps:

[0011] (1) mixing a chromium source, a sodium source and a complexing agent to obtain a gel;

[0012] (2) dehydrating the gel in step (1) to obtain a dry gel;

[0013] (3) performing primary decarburization and secondary decarburization on the dry gel in step (2) in sequence, and obtaining the sodium chromite material after sintering;

[0014] The dehydration temperature is T 0 The temperature of the first decarburization is T 1 , the temperature of secondary decarburization is T 2 The sintering temperature is T 3 , T 0 <T 1 <T 2 <T 3 ; The atmosphere of the secondary decarburization is an oxygen-containing atmosphere.

[0015] The present invention uses a chromium source and a sodium source as main raw materials, adopts a complexing agent to form a colloid, performs primary decarburization and secondary decarburization after dehydration, and sintering to obtain the carbon-coated sodium chromite material. The preparation method is simple in process, low in cost and mild in conditions, and partial decarburization is performed by step-by-step heating decarburization to achieve carbon coating of the sodium chromite material, which not only effectively prevents the occurrence of side reactions and improves the electrochemical stability and cycle performance of the material, but also the formed carbon coating layer can play the role of a conductive agent, and has good application potential.

[0016] The present invention adopts step-by-step heating decarburization, and the temperature of the first decarburization is slightly higher than the dehydration temperature, so that the complex can be decomposed. At the same time, in this process, the excess complexing agent that has not formed a complex is evaporated along with part of the water to form a dry gel, which is beneficial to the contact with the oxygen-containing atmosphere for decarburization during the second decarburization to prevent excessive carbon residue. The temperature of the second decarburization is slightly higher than the temperature of the first decarburization and lower than the sintering temperature, and the dry gel is heated in the oxygen-containing atmosphere, so that the organic matter in the complex can be converted into oxides and discharged with the gas to obtain a relatively pure solid mixture.

[0017] The complexing agent in the present invention refers to an organic compound that can form complex ions with metal ions and further gel the solution.

[0018] In the present invention, if secondary decarburization is not performed and sintering is performed directly after primary decarburization, partial decarburization cannot be achieved, and a large amount of residual carbon in the material remains in the product as an impurity, which not only fails to form a carbon coating of the sodium chromite material, but also seriously affects the capacity of the material, thereby failing to effectively improve the electrochemical properties of the material.

[0019] Preferably, the chromium source comprises chromium oxide.

[0020] Preferably, the chromium oxide includes any one of chromium oxide, chromium trioxide or chromium dioxide, or a combination of at least two thereof, preferably chromium trioxide.

[0021] Preferably, the sodium source includes any one of sodium hydroxide, sodium nitrate, sodium sulfate or sodium carbonate, or a combination of at least two thereof, preferably sodium carbonate.

[0022] In the present invention, sodium carbonate is stable at high temperature and does not decompose at the reaction temperature. The product is carbon dioxide, which is easy to separate.

[0023] Preferably, the complexing agent includes any one of organic acids, organic acid salts, amine compounds or ammonium compounds, or a combination of at least two of them.

[0024] Preferably, the organic acid comprises any one of oxalic acid, maleic acid, ascorbic acid, succinic acid, lactic acid, malic acid or citric acid, or a combination of at least two thereof, preferably citric acid.

[0025] Preferably, the organic acid salt comprises sodium citrate.

[0026] Preferably, the amine compound includes any one of ethanolamine, diethylamine or triethanolamine, or a combination of at least two of them.

[0027] Preferably, the ammonium compound comprises ammonium oxalate.

[0028] Preferably, the molar ratio of the chromium source, the sodium source and the complexing agent is 1:(1-2):(1.5-2.5), wherein the selection range of the sodium source 1-2 can be, for example, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 1.10, and the selection range of the complexing agent 1.5-2.5 can be, for example, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4 or 2.5, etc.

[0029] In the present invention, if the amount of the complexing agent is too small, the gel cannot be effectively prepared, the raw materials are easy to separate after the stirring is stopped, and the mixing effect is extremely poor; if the amount of the complexing agent is too large, the decarbonization difficulty in the subsequent steps becomes greater, and excessive carbon is easily left, which affects the electrochemical properties of the product, especially the capacity performance.

[0030] Preferably, the mixing method in step (1) is:

[0031] (a) preparing a sodium source solution;

[0032] (b) adding a chromium source and a complexing agent into the sodium source solution and mixing them.

[0033] The present invention adopts a liquid-solid mixing method of a sodium source solution, chromium oxide and a complexing agent, which greatly reduces the difficulty and time required for mixing. After mixing, the chromium source and the sodium source can achieve molecular-level contact. At the same time, under the protection of the gel, solid-liquid separation caused by precipitation will not occur, thereby ensuring a stable mixing state.

[0034] Preferably, the concentration of the sodium source solution is 1 g / L-saturation concentration, preferably saturation concentration.

[0035] In the present invention, the saturation concentration refers to the concentration of the solvent when a sodium source is added to the solvent until the sodium source can no longer be dissolved in the solvent. The concentration of the solvent at this time is the saturation concentration of the sodium source.

[0036] Preferably, the mixing process in step (1) is accompanied by stirring.

[0037] Preferably, the mixing temperature in step (1) is 20-80°C, for example, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C, etc., preferably 30-40°C.

[0038] In the present invention, the purpose of heating during the mixing process is to increase the solubility of the sodium source and increase the mixing amount.

[0039] Preferably, the mixing time in step (1) is 0.5-15 h, for example, 0.5 h, 3 h, 5 h, 7 h, 9 h, 11 h, 13 h or 15 h, etc., preferably 1-10 h.

[0040] Preferably, the dehydration method in step (2) includes any one of heating evaporation, vacuum drying or air drying, or a combination of at least two of them, preferably air drying.

[0041] Preferably, the dehydration temperature is 30-90°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or 90°C, etc., preferably 50-90°C.

[0042] In the present invention, after obtaining the gel, drying and dehydration are performed at 30-90° C., which can not only prevent excess water from affecting subsequent processes, but also avoid the complex from precipitating too quickly and affecting the mixing effect.

[0043] Preferably, the dehydration time is 0.5-15 h, for example, it can be 0.5 h, 3 h, 5 h, 7 h, 9 h, 11 h, 13 h or 15 h, etc., preferably 1-10 h.

[0044] Preferably, the atmosphere for the primary decarburization is an air atmosphere.

[0045] Preferably, the heating temperature for the primary decarburization is 150-200°C, for example, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, etc., preferably 160-190°C.

[0046] Preferably, the heating time for the primary decarburization is 1-24 h, for example, 1 h, 5 h, 10 h, 15 h, 20 h or 25 h, etc., preferably 12-24 h.

[0047] Preferably, the oxygen-containing atmosphere is oxygen, or a mixture of oxygen and protective gas.

[0048] Preferably, the protective gas comprises any one of nitrogen, helium, neon or argon, or a combination of at least two thereof, for example, a combination of nitrogen and helium, a combination of nitrogen and neon, a combination of nitrogen and argon, a combination of helium and neon, or a combination of neon and argon, preferably nitrogen.

[0049] Preferably, the volume fraction of oxygen in the mixture of oxygen and protective gas is 5-100% and does not include 100%, for example, it can be 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 99% and the like.

[0050] In the present invention, if the volume fraction of oxygen in the mixed gas of oxygen and protective gas is too small, decarburization takes a very long time and the effect is poor, and decarburization cannot be continued when the oxygen content is extremely low.

[0051] Preferably, the heating temperature of the secondary decarburization is 500-700°C, for example, it can be 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C, or 700°C, etc., preferably 520-650°C.

[0052] In the present invention, if the heating temperature of the secondary decarburization is too low, the decarburization effect is poor, and even decarburization cannot be performed at a relatively low temperature, and the required time is extremely long; if the heating temperature of the secondary decarburization is too high, partial oxidation of the raw material will result in the generation of hexavalent chromium impurities.

[0053] Preferably, the heating time for the secondary decarburization is 1-24 h, for example, 1 h, 5 h, 10 h, 15 h, 20 h or 25 h, etc., preferably 2-7 h.

[0054] In the present invention, if the heating time of the secondary decarbonization is too long, all the carbon is easily removed, and carbon coating cannot be produced after the subsequent steps; and after all the carbon is removed, the raw material is easily oxidized, causing the material ratio to change and producing raw material impurities that cannot react. If the heating time is too short, the material temperature rises insufficiently, the organic matter does not fully reach the reaction temperature, and the decarbonization effect can hardly be achieved.

[0055] The present invention does not limit the reaction equipment for primary decarburization and secondary decarburization. For example, it can be any one of a muffle furnace, a box furnace, a tube furnace, a belt furnace, a rotary kiln or a fluidized bed.

[0056] Preferably, the primary decarburization is followed by grinding, and the grinding is followed by secondary decarburization.

[0057] Preferably, the sintering atmosphere in step (3) is an inert atmosphere, and the gas in the inert atmosphere includes any one of nitrogen, helium, neon or argon, or a combination of at least two of them, for example, it can be a combination of nitrogen and helium, a combination of nitrogen and neon, a combination of nitrogen and argon, a combination of helium and neon, or a combination of neon and argon, preferably nitrogen.

[0058] Preferably, the sintering temperature is 850-950°C, for example, it can be 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C or 950°C, etc., preferably 870-920°C.

[0059] Preferably, the sintering time is 1-24 h, for example, 1 h, 5 h, 10 h, 15 h, 20 h or 25 h.

[0060] As a preferred technical solution, the preparation method comprises the following steps:

[0061] (I) mixing the prepared sodium source solution with the chromium source and the complexing agent at 20-80° C. and stirring for 0.5-15 hours to form a gel;

[0062] Wherein, the molar ratio of the chromium source, the sodium source and the complexing agent is 1:(1-2):(1.5-2.5);

[0063] (II) dehydrating the gel of step (I) at 30-90° C. for 0.5-15 h to obtain a dry gel;

[0064] (III) heating the dry gel of step (II) in an air atmosphere at 150-200° C. for 1-24 h, grinding it and heating it in an oxygen-containing atmosphere at 500-700° C. for 1-24 h, and then sintering it in an inert atmosphere at 850-950° C. for 1-24 h to obtain the carbon-coated sodium chromite material.

[0065] In a second aspect, the present invention provides a carbon-coated sodium chromite material prepared by the preparation method described in the first aspect, wherein the carbon-coated sodium chromite material comprises a sodium chromite core and a carbon coating layer located on the surface of the core.

[0066] The carbon-coated sodium chromite material prepared by the present invention can effectively reduce the occurrence of side reactions and improve the electrochemical stability and cycle performance of the material. On the other hand, since the carbon coating layer can act as a conductive agent, the use of conductive agents can be reduced and the cost can be reduced without reducing the electrochemical performance.

[0067] Preferably, the structure of the sodium chromite material is a hexagonal structure.

[0068] Preferably, the average particle size of the sodium chromite material is 1-5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.

[0069] In a third aspect, the present invention provides a sodium ion battery, wherein the positive electrode of the sodium ion battery comprises the carbon-coated sodium chromite material as described in the second aspect.

[0070] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0071] Compared with the prior art, the present invention has the following beneficial effects:

[0072] (1) The present invention provides a method for preparing a carbon-coated sodium chromite material. The method uses a chromium source and a sodium source as main raw materials, uses a complexing agent to form a colloid, performs primary decarburization and secondary decarburization after dehydration, and sintering to obtain the carbon-coated sodium chromite material. This preparation method uses a step-by-step heating decarburization method to perform partial decarburization, thereby achieving carbon coating of the sodium chromite material, which not only effectively prevents the occurrence of side reactions, but also forms a carbon coating layer with good uniformity, which can act as a conductive agent, improve the electrochemical stability and cycle performance of the material, and has good application potential.

[0073] (2) The preparation method provided by the present invention has strong controllability, simple process, low cost and mild reaction conditions, and is easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 This is a SEM image of the carbon-coated sodium chromite material provided in Example 1 of the present invention.

[0075] Figure 2 This is the XRD spectrum of the carbon-coated sodium chromite material provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0076] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0077] Example 1

[0078] The present invention provides a method for preparing a sodium chromite material, the preparation method comprising the following steps:

[0079] (1) dissolving 10.6 g of sodium carbonate in 20 mL of deionized water to obtain a saturated solution of sodium carbonate, and adding 15.2 g of chromium trioxide and 38.4 g of citric acid, mixing and stirring at 35° C. for 5 h to form a gel;

[0080] Wherein, the molar ratio of chromium trioxide, sodium carbonate and citric acid is 1:1:2;

[0081] (2) dehydrating the gel prepared in step (1) by air drying at 80° C. for 7 h to obtain a dry gel;

[0082] (3) The dry gel of step (2) is subjected to stepwise heating decarburization, firstly, it is heated in an air atmosphere at 150° C. for 24 h for primary decarburization, and after simple grinding, it is heated in a mixture of nitrogen and oxygen (oxygen volume fraction is 50%) at 500° C. for 4 h for secondary decarburization to obtain a mixture;

[0083] (4) The mixture of step (3) is loaded into a reaction apparatus, and nitrogen gas is introduced at a flow rate of 800 mL / min, the temperature program is set to 5°C / min, the sintering temperature is 930°C, and after keeping warm for 4 hours, the mixture is naturally cooled in the furnace to obtain a carbon-coated sodium chromite material with a hexagonal structure and an average particle size of 3 μm.

[0084] Figure 1 The SEM image of the carbon-coated sodium chromite material provided in this embodiment is shown. It can be seen from the image that the sodium chromite material is a hexagonal aggregate particle.

[0085] Figure 2 The XRD spectrum of the carbon-coated sodium chromite material provided in this embodiment is shown. It can be seen from the figure that the sodium chromite material has an O3-type layered oxide crystal structure.

[0086] Example 2

[0087] The present invention provides a method for preparing a sodium chromite material, the preparation method comprising the following steps:

[0088] (1) dissolving 10.6 g of sodium carbonate in 20 mL of deionized water to obtain a saturated solution of sodium carbonate, and adding 15.2 g of chromium trioxide and 18.1 g of oxalic acid, mixing and stirring at 30° C. for 10 h to form a gel;

[0089] Wherein, the molar ratio of chromium trioxide, sodium carbonate and oxalic acid is 1:1:2;

[0090] (2) dehydrating the gel prepared in step (1) by air drying at 70° C. for 8 h to obtain a dry gel;

[0091] (3) The dry gel of step (2) is subjected to stepwise heating decarburization, firstly, it is heated in an air atmosphere at 170° C. for 24 h for primary decarburization, and after simple grinding, it is heated in a mixed gas of helium and oxygen (oxygen volume fraction is 40%) at 600° C. for 4 h for secondary decarburization to obtain a mixture;

[0092] (4) The mixture of step (3) was loaded into a reaction apparatus, and nitrogen gas was introduced at a flow rate of 800 mL / min. The temperature program was set to 5°C / min, the sintering temperature was 920°C, and after keeping warm for 4 hours, the mixture was naturally cooled in the furnace to obtain a carbon-coated sodium chromite material with a hexagonal structure and an average particle size of 2.5 μm.

[0093] Example 3

[0094] The present invention provides a method for preparing a sodium chromite material, the preparation method comprising the following steps:

[0095] (1) dissolving 10.6 g of sodium carbonate in 20 mL of deionized water to obtain a saturated solution of sodium carbonate, and adding 15.2 g of chromium trioxide and 35.2 g of ascorbic acid, mixing and stirring at 40° C. for 3 h to form a gel;

[0096] Wherein, the molar ratio of chromium trioxide, sodium carbonate and ascorbic acid is 1:1:2;

[0097] (2) dehydrating the gel prepared in step (1) by air drying at 80° C. for 7 h to obtain a dry gel;

[0098] (3) The dry gel of step (2) is subjected to stepwise heating decarburization, firstly, it is heated in an air atmosphere at 150° C. for 24 h for primary decarburization, and after simple grinding, it is heated in a mixture of neon and oxygen (oxygen volume fraction is 30%) at 530° C. for 7 h for secondary decarburization to obtain a mixture;

[0099] (4) The mixture of step (3) is loaded into a reaction apparatus, and nitrogen gas is introduced at a flow rate of 800 mL / min, the temperature program is set to 5°C / min, the sintering temperature is 900°C, and after keeping warm for 5 hours, the mixture is naturally cooled in the furnace to obtain a carbon-coated sodium chromite material with a hexagonal structure and an average particle size of 3.5 μm.

[0100] Example 4

[0101] The present invention provides a method for preparing a sodium chromite material, the preparation method comprising the following steps:

[0102] (1) dissolving 10.6 g of sodium carbonate in 20 mL of deionized water to obtain a saturated solution of sodium carbonate, and adding 15.2 g of chromium trioxide and 23.2 g of maleic acid, mixing and stirring at 20° C. for 15 h to form a gel;

[0103] Wherein, the molar ratio of chromium trioxide, sodium carbonate and maleic acid is 1:1:2;

[0104] (2) dehydrating the gel prepared in step (1) by air drying at 80° C. for 7 h to obtain a dry gel;

[0105] (3) The dry gel of step (2) is subjected to stepwise heating decarburization, firstly, it is heated in an air atmosphere at 150° C. for 24 h for primary decarburization, and after simple grinding, it is heated in a mixed gas of argon and oxygen (oxygen volume fraction is 70%) at 520° C. for 3 h for secondary decarburization to obtain a mixture;

[0106] (4) The mixture of step (3) is loaded into a reaction apparatus, and nitrogen gas is introduced at a flow rate of 800 mL / min, the temperature program is set to 5°C / min, the sintering temperature is 940°C, and after keeping warm for 4 hours, the mixture is naturally cooled in the furnace to obtain a carbon-coated sodium chromite material with a hexagonal structure and an average particle size of 2 μm.

[0107] Example 5

[0108] The present invention provides a method for preparing a sodium chromite material, the preparation method comprising the following steps:

[0109] (1) dissolving 10.6 g of sodium carbonate in 20 mL of deionized water to obtain a saturated solution of sodium carbonate, and adding 15.2 g of chromium trioxide and 23.5 g of succinic acid, mixing and stirring at 60° C. for 2 h to form a gel;

[0110] Wherein, the molar ratio of chromium trioxide, sodium carbonate and succinic acid is 1:1:2;

[0111] (2) dehydrating the gel prepared in step (1) by air drying at 90° C. for 12 h to obtain a dry gel;

[0112] (3) The dry gel of step (2) is subjected to stepwise heating decarburization, firstly, it is heated in an air atmosphere at 190° C. for 18 h for primary decarburization, and after simple grinding, it is heated in a mixture of nitrogen and oxygen (oxygen volume fraction is 90%) at 600° C. for 2 h for secondary decarburization to obtain a mixture;

[0113] (4) The mixture of step (3) is loaded into a reaction apparatus, and nitrogen gas is introduced at a flow rate of 800 mL / min, the temperature program is set to 5°C / min, the sintering temperature is 950°C, and after keeping warm for 5 hours, the mixture is naturally cooled in the furnace to obtain a carbon-coated sodium chromite material with a hexagonal structure and an average particle size of 4 μm.

[0114] Example 6

[0115] The present invention provides a method for preparing a sodium chromite material, the preparation method comprising the following steps:

[0116] (1) dissolving 10.6 g of sodium carbonate in 20 mL of deionized water to obtain a saturated solution of sodium carbonate, and adding 15.2 g of chromium trioxide and 18.4 g of lactic acid, mixing and stirring at 70° C. for 1 h to form a gel;

[0117] Wherein, the molar ratio of chromium trioxide, sodium carbonate and lactic acid is 1:1:2;

[0118] (2) dehydrating the gel prepared in step (1) by air drying at 50° C. for 12 h to obtain a dry gel;

[0119] (3) decarburizing the dry gel in step (2) by heating in steps, firstly, decarburizing the dry gel in an air atmosphere at 200° C. for 14 h, then decarburizing the dry gel in a mixture of helium and oxygen (oxygen volume fraction is 70%) at 500° C. for 5 h after simple grinding, to obtain a mixture;

[0120] (4) The mixture of step (3) is loaded into a reaction apparatus, and nitrogen gas is introduced at a flow rate of 800 mL / min, the temperature program is set to 5°C / min, the sintering temperature is 890°C, and after keeping warm for 4 hours, the mixture is naturally cooled in the furnace to obtain a carbon-coated sodium chromite material with a hexagonal structure and an average particle size of 1.5 μm.

[0121] Example 7

[0122] The present invention provides a method for preparing a sodium chromite material, the preparation method comprising the following steps:

[0123] (1) dissolving 10.6 g of sodium carbonate in 20 mL of deionized water to obtain a saturated solution of sodium carbonate, and adding 15.2 g of chromium trioxide and 28.4 g of malic acid, mixing and stirring at 80° C. for 0.5 h to form a gel;

[0124] Wherein, the molar ratio of chromium trioxide, sodium carbonate and malic acid is 1:1:2.1;

[0125] (2) dehydrating the gel prepared in step (1) by air drying at 80° C. for 7 h to obtain a dry gel;

[0126] (3) The dry gel of step (2) is subjected to stepwise heating decarburization, firstly, it is heated in an air atmosphere at 150° C. for 24 h for primary decarburization, and after simple grinding, it is heated in a mixed gas of argon and oxygen (oxygen volume fraction is 40%) at 500° C. for 6 h for secondary decarburization to obtain a mixture;

[0127] (4) The mixture of step (3) is loaded into a reaction apparatus, and nitrogen gas is introduced at a flow rate of 800 mL / min, the temperature program is set to 5°C / min, the sintering temperature is 940°C, and after keeping warm for 6 hours, the mixture is naturally cooled in the furnace to obtain a carbon-coated sodium chromite material with a hexagonal structure and an average particle size of 4.5 μm.

[0128] Example 8

[0129] The present invention provides a method for preparing a sodium chromite material, the preparation method comprising the following steps:

[0130] (1) dissolving 8.5 g of sodium nitrate in deionized water to obtain a sodium nitrate solution with a concentration of 1 g / L, and adding 15.2 g of chromium trioxide and 64.5 g of sodium citrate, mixing and stirring at 20° C. for 15 h to form a gel;

[0131] Wherein, the molar ratio of chromium trioxide, sodium nitrate and sodium citrate is 1:1:2.5;

[0132] (2) vacuum drying the gel of step (1) at 30° C. for 15 h to dehydrate and obtain a dry gel;

[0133] (3) decarburizing the dry gel in step (2) by heating in steps, firstly decarburizing the dry gel in an air atmosphere at 150° C. for 24 h, then decarburizing the dry gel in an oxygen atmosphere at 700° C. for 1 h after simple grinding, to obtain a mixture;

[0134] (4) The mixture of step (3) is loaded into a reaction device, and helium gas is introduced at a flow rate of 800 mL / min, the temperature program is set to 5°C / min, the sintering temperature is 850°C, and after keeping warm for 24 hours, the mixture is naturally cooled in the furnace to obtain a carbon-coated sodium chromite material with a hexagonal structure and an average particle size of 1 μm.

[0135] Example 9

[0136] The present invention provides a method for preparing a sodium chromite material, the preparation method comprising the following steps:

[0137] (1) dissolving 21.3 g of sodium sulfate in deionized water to obtain a sodium sulfate solution with a concentration of 5 g / L, and adding 15.2 g of chromium trioxide and 12.2 g of ethanolamine, mixing and stirring at 50° C. for 8 h to form a gel;

[0138] Wherein, the molar ratio of chromium trioxide, sodium sulfate and ethanolamine is 1:1.5:2;

[0139] (2) dehydrating the gel prepared in step (1) by air drying at 60° C. for 5 h to obtain a dry gel;

[0140] (3) decarburizing the dry gel in step (2) by heating in steps, firstly decarburizing the dry gel in an air atmosphere at 175° C. for 12 h, then decarburizing the dry gel in a nitrogen and oxygen mixture (oxygen volume fraction is 50%) at 550° C. for 12 h after simple grinding, to obtain a mixture;

[0141] (4) The mixture of step (3) was loaded into a reaction apparatus, and argon gas was introduced at a flow rate of 800 mL / min. The temperature program was set to 5°C / min, the sintering temperature was 870°C, and after keeping warm for 12 hours, the mixture was naturally cooled in the furnace to obtain a carbon-coated sodium chromite material with a hexagonal structure and an average particle size of 3 μm.

[0142] Example 10

[0143] The present invention provides a method for preparing a sodium chromite material, the preparation method comprising the following steps:

[0144] (1) dissolving 21.2 g of sodium carbonate in deionized water to obtain a sodium carbonate solution with a concentration of 10 g / L, and adding 15.2 g of chromium trioxide and 18.6 g of ammonium oxalate, mixing and stirring at 80° C. for 0.5 h to form a gel;

[0145] Wherein, the molar ratio of chromium trioxide, sodium carbonate and ammonium oxalate is 1:2:1.5;

[0146] (2) dehydrating the gel prepared in step (1) by air drying at 90° C. for 0.5 h to obtain a dry gel;

[0147] (3) The dry gel of step (2) is subjected to stepwise heating decarburization, firstly, it is heated in an air atmosphere at 200° C. for 1 h for primary decarburization, and after simple grinding, it is heated in a mixture of nitrogen and oxygen (oxygen volume fraction is 50%) at 650° C. for 7 h for secondary decarburization to obtain a mixture;

[0148] (4) The mixture of step (3) is loaded into a reaction apparatus, and neon gas is introduced at a flow rate of 800 mL / min, the temperature program is set to 5°C / min, the sintering temperature is 950°C, and after keeping warm for 1 hour, the mixture is naturally cooled in the furnace to obtain a carbon-coated sodium chromite material with a hexagonal structure and an average particle size of 5 μm.

[0149] Embodiment 11

[0150] The difference between this embodiment and embodiment 1 is that the molar ratio of chromium trioxide, sodium carbonate and citric acid is 1:1:1.

[0151] The rest of the preparation methods and parameters were the same as those in Example 1.

[0152] Example 12

[0153] The difference between this embodiment and embodiment 1 is that the molar ratio of chromium trioxide, sodium carbonate and citric acid is 1:1:3.

[0154] The rest of the preparation methods and parameters were the same as those in Example 1.

[0155] Embodiment 13

[0156] The difference between this embodiment and embodiment 1 is that the volume fraction of oxygen in the mixed gas of nitrogen and oxygen in step (3) is 3%.

[0157] The rest of the preparation methods and parameters were the same as those in Example 1.

[0158] Embodiment 14

[0159] The difference between this embodiment and embodiment 1 is that the heating temperature for the secondary decarburization in step (3) is 450°C.

[0160] The rest of the preparation methods and parameters were the same as those in Example 1.

[0161] Embodiment 15

[0162] The difference between this embodiment and embodiment 1 is that the heating temperature of the secondary decarburization in step (3) is 725°C.

[0163] The rest of the preparation methods and parameters were the same as those in Example 1.

[0164] Example 16

[0165] The difference between this embodiment and embodiment 1 is that the sintering temperature in step (4) is 500°C.

[0166] The rest of the preparation methods and parameters were the same as those in Example 1.

[0167] Comparative Example 1

[0168] The difference between this comparative example and Example 1 is that in step (1), sodium carbonate is directly mixed with chromium oxide and citric acid in a solid phase, and step (3) is directly performed after mixing.

[0169] The rest of the preparation methods and parameters were the same as those in Example 1.

[0170] Comparative Example 2

[0171] The difference between this comparative example and Example 1 is that no citric acid is added in step (1).

[0172] The rest of the preparation methods and parameters were the same as those in Example 1.

[0173] Comparative Example 3

[0174] The difference between this comparative example and Example 1 is that step (2) is not performed.

[0175] The rest of the preparation methods and parameters were the same as those in Example 1.

[0176] Comparative Example 4

[0177] The difference between this comparative example and Example 1 is that the secondary decarburization in step (3) is not performed.

[0178] The rest of the preparation methods and parameters were the same as those in Example 1.

[0179] Comparative Example 5

[0180] The difference between this comparative example and Example 1 is that the temperature of the first decarburization in step (3) is 600° C., that is, the temperature of the first decarburization is greater than the temperature of the second decarburization.

[0181] The rest of the preparation methods and parameters were the same as those in Example 1.

[0182] Comparative Example 6

[0183] The difference between this comparative example and Example 1 is that the atmosphere for the secondary decarburization in step (3) is a nitrogen atmosphere.

[0184] The rest of the preparation methods and parameters were the same as those in Example 1.

[0185] Performance Testing

[0186] The carbon-coated sodium chromite material provided in Example 1-16 and Comparative Example 1-6 was mixed with acetylene black and polyvinylidene fluoride in a molar ratio of 8.5:0.5:1, and then an organic solvent N-methylpyrrolidone was added as a dispersant. After mixing, the mixture was evenly coated on an aluminum foil, and then placed in a blast drying oven at 80°C for 6-12 hours. After baking, the cathode sheet with a diameter of 14 mm was punched out. A metal sodium sheet was used as a negative electrode, a glass fiber was used as a diaphragm, and 1 mol / L sodium hexafluorophosphate and propylene carbonate:ethylene carbonate = 1:1 were used as electrolytes. A battery was assembled in a glove box filled with high-purity argon gas with an oxygen pressure and a water pressure both below 1 ppm, and a charge and discharge test was performed on a battery test system. The current density during the test was 125 mA / g, and the voltage range was 2.4-3.6 V.

[0187] The test results are shown in Table 1.

[0188] Table 1

[0189]

[0190]

[0191] analyze:

[0192] It can be seen from the data results of Examples 1-10 that the present invention mixes chromium oxide and sodium carbonate by a gel method and then sinters to obtain a carbon-coated sodium chromite material. By optimizing the type and amount of the complexing agent and the adjustment of parameters in the decarburization, the reaction efficiency is improved while providing a carbon source for generating a carbon coating layer. The reaction process is highly controllable, the obtained material has a uniform phase and a narrow particle size distribution, is easy to realize large-scale production, and has high economic benefits.

[0193] By comparing the data results of Example 1 with those of Examples 11-12, it can be seen that when the molar ratio of the chromium source, the sodium source and the complexing agent is too large, that is, the amount of the complexing agent is too small, it will be difficult for the solution to form a stable gel, resulting in the separation of the raw materials after the stirring is stopped, and the purpose of uniform mixing cannot be achieved, and the battery performance is poor; when the molar ratio of the chromium source, the sodium source and the complexing agent is too small, that is, the amount of the complexing agent is too large, the gel will contain too much organic matter, which will increase the difficulty of decarbonization, not only greatly increase the decarbonization reaction time, but also easily cause excess residual carbon to be unable to be removed, affecting the performance of the battery.

[0194] By comparing the data results of Example 1 with those of Example 13, it can be seen that when the volume fraction of oxygen in the mixture of oxygen and nitrogen is too small, the oxygen does not have sufficient contact with the reactants, resulting in failure to achieve the expected decarbonization amount within the reaction time, making it difficult to effectively improve the performance of the battery.

[0195] By comparing the data results of Example 1 with those of Examples 14-15, it can be seen that when the heating temperature of the secondary decarburization is too low, decarburization can hardly occur, or the decarburization amount is extremely low, resulting in excessive residual carbon; when the heating temperature of the secondary decarburization is too high, the decarburization speed is too fast and difficult to control, and the raw materials are easily oxidized after complete decarburization, resulting in the generation of hexavalent chromium impurities in the raw materials, which can easily affect the material battery performance.

[0196] From the comparison of the data results of Example 1 and Example 16, it can be seen that the sintering temperature is too low and the driving force is insufficient, so the target material, that is, the carbon-coated sodium chromite material is difficult to generate.

[0197] From the comparison of the data results of Example 1 and Comparative Example 1, it can be seen that simple solid phase mixing will cause the chromium oxide and sodium carbonate to not be fully mixed, resulting in part of the citric acid not participating in the reaction and existing as an impurity phase in the product. The specific capacity is reduced to 63 mAh / g, and the cycle stability and capacity retention rate are also significantly reduced.

[0198] From the comparison of the data results of Example 1 and Comparative Example 2, it can be seen that due to the absence of citric acid addition, sodium carbonate precipitates after drying to remove most of the water, forming an inhomogeneous mixture with chromium oxide, the degree of contact is poor, and the reaction is incomplete after sintering in an inert atmosphere, resulting in the product containing unreacted raw materials, so the specific capacity, cycle stability and capacity retention rate are seriously reduced.

[0199] By comparing the data results of Example 1 and Comparative Example 3, it can be seen that since no dehydration is performed, the raw material is in a gel state containing a large amount of water for step-by-step decarbonization. During the step-by-step decarbonization process, the water hinders the decomposition and removal of organic matter, so the decarbonization effect is poor, and the product still contains a large amount of carbon. The specific capacity, cycle stability and capacity retention rate show a significant downward trend.

[0200] From the comparison of the data results of Example 1 and Comparative Example 4, it can be seen that without secondary decarbonization, a large amount of organic matter will remain in the gel and is difficult to discharge, so it cannot be used as a battery material.

[0201] By comparing the data results of Example 1 and Comparative Example 5, it can be seen that when the temperature of the secondary decarburization is lower than the temperature of the primary decarburization, due to the high temperature of the primary decarburization, a large amount of organic matter is converted into gas, generating irritating gas, which is extremely polluting to the environment. In addition, since both decarburizations are performed at relatively high temperatures, the raw materials are oxidized after complete decarburization to generate impurities. Therefore, when the product is used as an electrode material, the capacity and cycle stability are reduced.

[0202] By comparing the data results of Example 1 with those of Comparative Example 7, it can be seen that when the atmosphere for secondary decarburization is a nitrogen atmosphere, decarburization is impossible due to the absence of oxygen to participate in the reaction, so all the organic matter in the gel remains and enters the product, the amount of impurities increases, and the capacity of the material is greatly reduced.

[0203] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a carbon-coated sodium chromite material, characterized in that: The preparation method includes the following steps: (1) Mix a chromium source, a sodium source, and a complexing agent to obtain a gel; (2) Dehydrate the gel obtained in step (1) to obtain a dry gel; (3) Perform primary decarbonization and secondary decarbonization on the dry gel obtained in step (2) in sequence, and obtain the sodium chromite material after sintering; The temperature of the dehydration is T0, the temperature of the primary decarbonization is T1, the temperature of the secondary decarbonization is T2, and the temperature of the sintering is T3, where T0 < T1 < T2 < T3; the atmosphere of the secondary decarbonization is an oxygen-containing atmosphere.

2. The preparation method according to claim 1, characterized in that: The chromium source includes chromium oxides.

3. The preparation method according to claim 2, characterized in that: The chromium oxides include any one or a combination of at least two of chromium monoxide, chromium(III) oxide, or chromium dioxide.

4. The preparation method according to claim 3, characterized in that: The chromium oxide is chromium(III) oxide.

5. The preparation method according to claim 1, characterized in that: The sodium source includes any one or a combination of at least two of sodium hydroxide, sodium nitrate, sodium sulfate, or sodium carbonate.

6. The preparation method according to claim 5, characterized in that: The sodium source is sodium carbonate.

7. The preparation method according to claim 1, characterized in that: The complexing agent includes any one or a combination of at least two of organic acids, organic acid salts, amine compounds, or ammonium compounds.

8. The preparation method according to claim 7, characterized in that: The organic acids include any one or a combination of at least two of oxalic acid, maleic acid, ascorbic acid, succinic acid, lactic acid, malic acid, or citric acid.

9. The preparation method according to claim 8, characterized in that: The organic acid is citric acid.

10. The preparation method according to claim 7, characterized in that: The organic acid salt includes sodium citrate.

11. The preparation method according to claim 7, characterized in that: The amine compounds include any one or a combination of at least two of ethanolamine, diethylamine, or triethanolamine.

12. The preparation method according to claim 7, characterized in that: The ammonium compound includes ammonium oxalate.

13. The preparation method according to claim 1, characterized in that: The molar ratio of the chromium source, the sodium source, and the complexing agent is 1:(1 - 2):(1.5 - 2.5).

14. The preparation method according to claim 1, characterized in that: The method of mixing in step (1) is as follows: (a) Prepare a sodium source solution; (b) Add the chromium source and the complexing agent to the sodium source solution for mixing.

15. The preparation method according to claim 14, characterized in that: The concentration of the sodium source solution is 1 g / L - saturated concentration.

16. The preparation method according to claim 15, characterized in that: The concentration of the sodium source solution is saturated concentration.

17. The preparation method according to claim 1, characterized in that: Stirring is accompanied during the mixing in step (1).

18. The preparation method according to claim 15, characterized in that: The temperature of the mixing in step (1) is 20 - 80 °C.

19. The preparation method according to claim 18, characterized in that: The temperature of the mixing in step (1) is 30 - 40 °C.

20. The preparation method according to claim 1, characterized in that: The time of the mixing in step (1) is 0.5 - 15 h.

21. The preparation method according to claim 20, characterized in that: The time of the mixing in step (1) is 1 - 10 h.

22. The preparation method according to claim 1, characterized in that: The method of dehydration in step (2) includes any one or a combination of at least two of heating evaporation, vacuum drying, or air drying.

23. The preparation method according to claim 22, characterized in that: The method of dehydration in step (2) is air drying.

24. The preparation method according to claim 1, characterized in that: The temperature of the dehydration is 30 - 90 °C.

25. The preparation method according to claim 24, characterized in that: The temperature of the dehydration is 50 - 90 °C.

26. The preparation method according to claim 1, characterized in that: The time of the dehydration is 0.5 - 15 h.

27. The preparation method according to claim 26, characterized in that: The time of the dehydration is 1 - 10 h.

28. The preparation method according to claim 1, characterized in that: The atmosphere of the primary decarbonization is an air atmosphere.

29. The preparation method according to claim 1, characterized in that: The heating temperature of the primary decarbonization is 150 - 200 °C.

30. The preparation method according to claim 29, characterized in that: The heating temperature of the primary decarbonization is 160 - 190 °C.

31. The preparation method according to claim 1, characterized in that: The heating time of the primary decarbonization is 1 - 24 h.

32. The preparation method according to claim 31, characterized in that: The heating time of the primary decarbonization is 12 - 24 h.

33. The preparation method according to claim 1, characterized in that: The oxygen-containing atmosphere is oxygen, or a mixture of oxygen and a protective gas.

34. The preparation method according to claim 33, characterized in that: The protective gas includes any one or a combination of at least two of nitrogen, helium, neon, or argon.

35. The preparation method according to claim 34, characterized in that: The protective gas is nitrogen.

36. The preparation method according to claim 33, characterized in that: In the mixture of oxygen and the protective gas, the volume fraction of oxygen is 5 - 100% and does not include 100%.

37. The preparation method according to claim 1, characterized in that The heating temperature of the secondary decarburization is 500-700°C.

38. The preparation method according to claim 37, characterized in that: The heating temperature of the secondary decarburization is 520-650°C.

39. The preparation method according to claim 1, characterized in that: The heating time of the secondary decarburization is 1-24h.

40. The preparation method according to claim 39, characterized in that: The heating time of the secondary decarburization is 2-7h.

41. The preparation method according to claim 1, characterized in that The primary decarburization is followed by grinding, and the grinding is followed by secondary decarburization.

42. The preparation method according to claim 1, characterized in that The sintering atmosphere in step (3) is an inert atmosphere, and the gas in the inert atmosphere includes any one of nitrogen, helium, neon or argon, or a combination of at least two of them.

43. The preparation method according to claim 42, characterized in that: The gas in the inert atmosphere is nitrogen.

44. The preparation method according to claim 1, characterized in that The sintering temperature is 850-950°C.

45. The preparation method according to claim 44, characterized in that: The sintering temperature is 870-920°C.

46. ​​The preparation method according to claim 1, characterized in that The sintering time is 1-24h.

47. The preparation method according to claim 1, characterized in that The preparation method comprises the following steps: (I) mixing the prepared sodium source solution with the chromium source and the complexing agent at 20-80° C. and stirring for 0.5-15 hours to form a gel; Wherein, the molar ratio of the chromium source, the sodium source and the complexing agent is 1:(1-2):(1.5-2.5); (II) dehydrating the gel of step (I) at 30-90° C. for 0.5-15 h to obtain a dry gel; (III) heating the dry gel of step (II) in an air atmosphere at 150-200° C. for 1-24 h, grinding it and heating it in an oxygen-containing atmosphere at 500-700° C. for 1-24 h, and then sintering it in an inert atmosphere at 850-950° C. for 1-24 h to obtain the carbon-coated sodium chromite material.

48. A carbon-coated sodium chromite material prepared by the preparation method according to any one of claims 1 to 47, characterized in that: The carbon-coated sodium chromite material comprises a sodium chromite core and a carbon coating layer located on the surface of the core.

49. The carbon-coated sodium chromite material according to claim 48, characterized in that The structure of the sodium chromite material is a hexagonal crystal structure.

50. The carbon-coated sodium chromite material according to claim 49, characterized in that The average particle size of the sodium chromite material is 1-5 μm.

51. A sodium ion battery, characterized in that: The positive electrode of the sodium ion battery includes the carbon-coated sodium chromite material as described in any one of claims 48-50.

Citation Information

Patent Citations

  • Method for producing sodium chromite

    CN103370277B

  • Method for preparing sodium chromite through vacuum method

    CN114180628A

  • Flexible self-supporting positive electrode for sodium ion battery as well as preparation method and application of flexible self-supporting positive electrode

    CN114530573A

  • NaCrO2 positive electrode material based on oxygen vacancy regulation and control as well as preparation method and application of NaCrO2 positive electrode material

    CN115215373A